Biological features of novel avian influenza A (H7N9) virus - Zhou, Jianfang; Wang, Dayan; Gao, Rongbao; Zhao, Baihui; Song, Jingdong; Qi, Xian; Zhang, Yanjun; Shi, Yonglin; Yang, Lei; Zhu, Wenfei; Bai, Tian; Qin, Kun; et al. (Nature (London), 2013)
An initial characterization of the receptor-binding properties of the novel avian influenza A (H7N9) shows that the virus has acquired the ability to bind human receptors while retaining the ability to bind avian receptors; the virus infects epithelial cells in the human lower respiratory tract and type II pneumocytes in the alveoli, and hypercytokinaemia was seen in infected patients. H7N9 avian flu virus isolates examined The H7N9 avian flu virus emerged in the human population on mainland China in February 2013, and by the first week of July WHO had recorded 133 cases including 43 deaths. Most cases so far have been linked to live bird markets. In this issue of Nature two groups report on the receptor-binding properties of H7N9. Both find that the virus has acquired the ability to bind the human α-2,3-linked sialic acid receptor yet has a retained preference for binding to the avian 2,3-linked receptor, a factor that may restrict its further evolution towards efficient transmission between humans. Steven Gamblin and colleagues also solve the crystal structure of the H7 haemagglutinin in complex with the receptor analogues, revealing details of how the human-receptor-binding properties may have arisen. Yuelong Shu and colleagues examine the pattern of virus infection in lung tissue. In human tracheal and lung explants, the virus infects epithelial cells in the lower respiratory tract and type II pneumocytes in the alveoli, and is better able to replicate in the lower respiratory tract compared with the trachea, a possible factor in the inefficient human-to-human transmission seen to date. They also report hypercytokinaemia in some patients — a cytokine storm that can contribute to disease severity — comparable to that seen in some H5N1 infections. Human infection associated with a novel reassortant avian influenza H7N9 virus has recently been identified in China 1 . A total of 132 confirmed cases and 39 deaths have been reported 2 . Most patients presented with severe pneumonia and acute respiratory distress syndrome 3 , 4 . Although the first epidemic has subsided, the presence of a natural reservoir and the disease severity highlight the need to evaluate its risk on human public health and to understand the possible pathogenesis mechanism. Here we show that the emerging H7N9 avian influenza virus poses a potentially high risk to humans. We discover that the H7N9 virus can bind to both avian-type (α2,3-linked sialic acid) and human-type (α2,6-linked sialic acid) receptors. It can invade epithelial cells in the human lower respiratory tract and type II pneumonocytes in alveoli, and replicated efficiently in ex vivo lung and trachea explant culture and several mammalian cell lines. In acute serum samples of H7N9-infected patients, increased levels of the chemokines and cytokines IP-10, MIG, MIP-1β, MCP-1, IL-6, IL-8 and IFN-α were detected. We note that the human population is naive to the H7N9 virus, and current seasonal vaccination could not provide protection.